Ukrainian television after the regaining of independence - Rudenko, M.; Smal, K. (ХДАК, 2023)
The history of Ukrainian television after the restoration of Ukraine’s independence in 1991 is mainly a story about the struggle for the Ukrainian language on the air, about how in the 1990s, Ukrainian television started as Ukrainian-language television, but in the 2000s, there was less and less Ukrainian-language content on Ukrainian television, and only at the end of the 2010s, after the introduction of language quotas for Ukrainian- language TV products, there was a gradual return to the Ukrainian-language TV space and the first Ukrainian TV series were created.
Keywords: телебачення, the television